Synthesis of 3-((4-Hydroxyphenyl)amino)propanoic Acid Derivatives as Promising Scaffolds for the Development of Antimicrobial Candidates Targeting Multidrug-Resistant Bacterial and Fungal Pathogens - Povilas Kavaliauskas; Birutė Grybaitė; Birutė Sapijanskaitė-Banevič; Rita Vaickelionienė; Vidmantas Petraitis; Rūta Petraitienė; Ethan Naing; Andrew Garcia; Ramunė Grigalevičiūtė; Vytautas Mickevičius (MDPI AG, 2024)
Infections caused by multidrug-resistant bacterial and fungal pathogens represent a significant global health concern, contributing to increased morbidity and mortality rates. Therefore, it is crucial to develop novel compounds targeting drug-resistant microbial strains. Herein, we report the synthesis of amino acid derivatives bearing an incorporated 4-hydroxyphenyl moiety with various substitutions. The resultant novel 3-((4-hydroxyphenyl)amino)propanoic acid derivatives 2-37 exhibited structure-dependent antimicrobial activity against both ESKAPE group bacteria and drug-resistant Candida species. Furthermore, these derivatives demonstrated substantial activity against Candida auris, with minimum inhibitory concentrations ranging from 0.5 to 64 µg/mL. Hydrazones 14-16, containing heterocyclic substituents, showed the most potent and broad-spectrum antimicrobial activity. This activity extended to methicillin-resistant Staphylococcus aureus (MRSA) with MIC values ranging from 1 to 8 µg/mL, vancomycin-resistant Enterococcus faecalis (0.5-2 µg/mL), Gram-negative pathogens (MIC 8-64 µg/mL), and drug-resistant Candida species (MIC 8-64 µg/mL), including Candida auris. Collectively, these findings underscore the potential utility of the novel 3-((4-hydroxyphenyl)amino)propanoic acid scaffold for further development as a foundational platform for novel antimicrobial agents targeting emerging and drug-resistant bacterial and fungal pathogens.